Plan de marketing para el desarrollo de un sistema Delivery en el Minimarket Don Omar, del sector Norte de Guayaquil - Giraldo León, Jaci Aylin (2023)
The present study focuses on designing and developing a strategic marketing plan to implement a delivery system at Minimarket Don Omar, located in the northern sector of Guayaquil. With the growing demand for delivery services and changes in consumer habits, the business faces the challenge of adapting to these trends to maintain competitiveness and meet customer expectations. The aim of this thesis is to provide a detailed and applicable guide for successfully entering the delivery market with a solid foundation and prospects for sustainable growth. The marketing plan is based on a comprehensive analysis of the environment, competition, and consumers, identifying specific opportunities and challenges........